If a parabola whose length of latus rectum is 4a touches both coordinate axis then find the locus of its focus.
a) ${{x}^{2}}{{y}^{2}}={{a}^{2}}\left( {{x}^{2}}+{{y}^{2}} \right)$
b) ${{x}^{2}}{{y}^{2}}={{a}^{2}}\left( {{x}^{2}}-{{y}^{2}} \right)$
c) ${{x}^{2}}{{y}^{2}}={{a}^{3}}\left( {{x}^{3}}+{{y}^{2}} \right)$
d) None of these
Answer
Verified
125.1k+ views
Hint: Consider the point on parabola in the form of $(a{{t}^{2}},2at)$ and draw tangents to the parabola. Then, we can use the distance between focus given by $(a,0)$ and tangents to formulate equations. The two tangents drawn to the parabola will be perpendicular to each other, so we can apply conditions for slopes of perpendicular lines to solve further.
Complete step-by-step solution -
It is given that the latus rectum is $4a$. So, let the given parabola ${{y}^{2}}=4ax$. Let the graph of parabola be like that which cuts both coordinates at A and B.
Let a point on parabola be $(a{{t}^{2}},2at)$. We have to find $\dfrac{dy}{dx}$ of the curve at a given point. Slope of tangent to given point $(a{{t}^{2}},2at)$ $=\dfrac{dy}{dx}$.
${{y}^{2}}=4ax$
We know $\dfrac{d{{x}^{n}}}{dx}=n{{x}^{n-1}}$, so we get
$2y\dfrac{dy}{dx}=4a$
The given point is $(a{{t}^{2}},2at)$, so, $y=2at$
$\begin{align}
& \dfrac{dy}{dx}=\dfrac{4a}{2(2at)} \\
& \dfrac{dy}{dx}=\dfrac{1}{t} \\
\end{align}$
So the slope of tangent passes through point $(a{{t}^{2}},2at)$ is $=\dfrac{1}{t}\ldots \ldots \left( 1 \right)$
Now, we can substitute the points and the slope write the equation of tangent using the formula $y-{{y}_{1}}=m(x-{{x}_{1}})$ as
$\begin{align}
& y-2at=\dfrac{1}{t}(x-a{{t}^{2}}) \\
& t\left( y-2at \right)=x-a{{t}^{2}} \\
& ty-2a{{t}^{2}}=x-a{{t}^{2}} \\
& x-ty+a{{t}^{2}}=0 \\
\end{align}$
Let A $(a{{s}^{2}},2as)$ be a point on the parabola, on the x-axis. So, from the above discussion and using equation (1), we can conclude that the slope of tangent passing through $(a{{s}^{2}},2as)$ is $=\dfrac{1}{s}$. We can substitute it in the equation of tangent and we get $x-sy+a{{s}^{2}}=0$.
Now, we know the focus of parabola ${{y}^{2}}=4ax$ must be at $(a,0)$. Then the distance of focus from the tangent of the equation $x-sy+a{{s}^{2}}=0$ can be calculated using the formula of distance of a point from line. If we have a line $ax+by+c=0$, then the perpendicular distance from a point $(x,y)$ to line is given by $d=\left| \dfrac{xa+yb+c}{\sqrt{{{a}^{2}}+{{b}^{2}}}} \right|$.
Now let the distance from focus point $(a,0)$ be x. Then we have,
$\begin{align}
& x=\left| \dfrac{a-0+a{{s}^{2}}}{\sqrt{{{1}^{2}}+{{s}^{2}}}} \right| \\
& x=\left| \dfrac{a\left( 1+{{s}^{2}} \right)}{\sqrt{{{1}^{2}}+{{s}^{2}}}} \right| \\
& x=\left| a\sqrt{{{1}^{2}}+{{s}^{2}}} \right|\ldots \ldots \ldots \left( 2 \right) \\
\end{align}$
Similarly, let B $(a{{r}^{2}},2ar)$ be a point on the parabola, on the y-axis. So, from the above discussion and using equation (1), we can conclude that the slope of tangent passing through $(a{{r}^{2}},2ar)$ is $=\dfrac{1}{r}$. We can substitute it in the equation of tangent and we get $x-ry+a{{r}^{2}}=0$.
Similarly, we can find the distance from focus point $(a,0)$ as $y$. So, we will get
$\begin{align}
& y=\left| \dfrac{a-0+a{{r}^{2}}}{\sqrt{{{1}^{2}}+{{r}^{2}}}} \right| \\
& y=\left| \dfrac{a\left( 1+{{r}^{2}} \right)}{\sqrt{{{1}^{2}}+{{r}^{2}}}} \right| \\
& y=\left| a\sqrt{{{1}^{2}}+{{r}^{2}}} \right|\ldots \ldots \ldots \left( 3 \right) \\
\end{align}$
Now, we know that the tangents are perpendicular to each other. So, the product of their slope is equal to -1. Applying it, we will get
$\dfrac{1}{r}\times \dfrac{1}{s}=-1$
$rs=-1\ldots \ldots \ldots \left( 4 \right)$
Now using equation (2), we get
$\begin{align}
& \dfrac{x}{a}=\left( \sqrt{{{1}^{2}}+{{s}^{2}}} \right) \\
& {{\left( \dfrac{x}{a} \right)}^{2}}=\left( {{1}^{2}}+{{s}^{2}} \right) \\
& {{\left( \dfrac{x}{a} \right)}^{2}}-1={{s}^{2}}\ldots \ldots \ldots \left( 5 \right) \\
\end{align}$
Now using equation (3), we get
$\begin{align}
& \dfrac{y}{a}=\left( \sqrt{{{1}^{2}}+{{r}^{2}}} \right) \\
& {{\left( \dfrac{y}{a} \right)}^{2}}=\left( {{1}^{2}}+{{r}^{2}} \right) \\
& {{\left( \dfrac{y}{a} \right)}^{2}}-1={{r}^{2}}\ldots \ldots \ldots \left( 6 \right) \\
\end{align}$
Multiplying equation (5) and (6), we get
$\begin{align}
& \left( {{\left( \dfrac{y}{a} \right)}^{2}}-1 \right)\left( {{\left( \dfrac{x}{a} \right)}^{2}}-1 \right)={{r}^{2}}{{s}^{2}} \\
& \left( {{\dfrac{y}{{{a}^{2}}}}^{2}}-1 \right)\left( {{\dfrac{x}{{{a}^{2}}}}^{2}}-1 \right)={{r}^{2}}{{s}^{2}} \\
\end{align}$
Now, simplifying terms inside bracket and using equation (4), we get
$\begin{align}
& \dfrac{{{x}^{2}}{{y}^{2}}}{{{a}^{2}}{{a}^{2}}}-\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{a}^{2}}}+1={{(-1)}^{2}} \\
& \dfrac{{{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})}{{{a}^{4}}}+1=1 \\
& \dfrac{{{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})}{{{a}^{4}}}=0 \\
& {{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})=0 \\
& {{x}^{2}}{{y}^{2}}={{a}^{2}}({{x}^{2}}+{{y}^{2}}) \\
\end{align}$
A parabola whose length of latus rectum is 4a touches both coordinate axis then the locus of its focus is ${{x}^{2}}{{y}^{2}}={{a}^{2}}({{x}^{2}}+{{y}^{2}})$.
So, the correct option must be a).
Note: Equation of a tangent to a parabola passing through point $(a{{t}^{2}},2at)$ can be taken as $x-ty+a{{t}^{2}}=0$ directly instead of deriving it. We must memorise this as it is very helpful in solving such questions and it will save time in the exam. In this question, latus rectum value is given through which we can find the focus of parabola and its equation.
Complete step-by-step solution -
It is given that the latus rectum is $4a$. So, let the given parabola ${{y}^{2}}=4ax$. Let the graph of parabola be like that which cuts both coordinates at A and B.
Let a point on parabola be $(a{{t}^{2}},2at)$. We have to find $\dfrac{dy}{dx}$ of the curve at a given point. Slope of tangent to given point $(a{{t}^{2}},2at)$ $=\dfrac{dy}{dx}$.
${{y}^{2}}=4ax$
We know $\dfrac{d{{x}^{n}}}{dx}=n{{x}^{n-1}}$, so we get
$2y\dfrac{dy}{dx}=4a$
The given point is $(a{{t}^{2}},2at)$, so, $y=2at$
$\begin{align}
& \dfrac{dy}{dx}=\dfrac{4a}{2(2at)} \\
& \dfrac{dy}{dx}=\dfrac{1}{t} \\
\end{align}$
So the slope of tangent passes through point $(a{{t}^{2}},2at)$ is $=\dfrac{1}{t}\ldots \ldots \left( 1 \right)$
Now, we can substitute the points and the slope write the equation of tangent using the formula $y-{{y}_{1}}=m(x-{{x}_{1}})$ as
$\begin{align}
& y-2at=\dfrac{1}{t}(x-a{{t}^{2}}) \\
& t\left( y-2at \right)=x-a{{t}^{2}} \\
& ty-2a{{t}^{2}}=x-a{{t}^{2}} \\
& x-ty+a{{t}^{2}}=0 \\
\end{align}$
Let A $(a{{s}^{2}},2as)$ be a point on the parabola, on the x-axis. So, from the above discussion and using equation (1), we can conclude that the slope of tangent passing through $(a{{s}^{2}},2as)$ is $=\dfrac{1}{s}$. We can substitute it in the equation of tangent and we get $x-sy+a{{s}^{2}}=0$.
Now, we know the focus of parabola ${{y}^{2}}=4ax$ must be at $(a,0)$. Then the distance of focus from the tangent of the equation $x-sy+a{{s}^{2}}=0$ can be calculated using the formula of distance of a point from line. If we have a line $ax+by+c=0$, then the perpendicular distance from a point $(x,y)$ to line is given by $d=\left| \dfrac{xa+yb+c}{\sqrt{{{a}^{2}}+{{b}^{2}}}} \right|$.
Now let the distance from focus point $(a,0)$ be x. Then we have,
$\begin{align}
& x=\left| \dfrac{a-0+a{{s}^{2}}}{\sqrt{{{1}^{2}}+{{s}^{2}}}} \right| \\
& x=\left| \dfrac{a\left( 1+{{s}^{2}} \right)}{\sqrt{{{1}^{2}}+{{s}^{2}}}} \right| \\
& x=\left| a\sqrt{{{1}^{2}}+{{s}^{2}}} \right|\ldots \ldots \ldots \left( 2 \right) \\
\end{align}$
Similarly, let B $(a{{r}^{2}},2ar)$ be a point on the parabola, on the y-axis. So, from the above discussion and using equation (1), we can conclude that the slope of tangent passing through $(a{{r}^{2}},2ar)$ is $=\dfrac{1}{r}$. We can substitute it in the equation of tangent and we get $x-ry+a{{r}^{2}}=0$.
Similarly, we can find the distance from focus point $(a,0)$ as $y$. So, we will get
$\begin{align}
& y=\left| \dfrac{a-0+a{{r}^{2}}}{\sqrt{{{1}^{2}}+{{r}^{2}}}} \right| \\
& y=\left| \dfrac{a\left( 1+{{r}^{2}} \right)}{\sqrt{{{1}^{2}}+{{r}^{2}}}} \right| \\
& y=\left| a\sqrt{{{1}^{2}}+{{r}^{2}}} \right|\ldots \ldots \ldots \left( 3 \right) \\
\end{align}$
Now, we know that the tangents are perpendicular to each other. So, the product of their slope is equal to -1. Applying it, we will get
$\dfrac{1}{r}\times \dfrac{1}{s}=-1$
$rs=-1\ldots \ldots \ldots \left( 4 \right)$
Now using equation (2), we get
$\begin{align}
& \dfrac{x}{a}=\left( \sqrt{{{1}^{2}}+{{s}^{2}}} \right) \\
& {{\left( \dfrac{x}{a} \right)}^{2}}=\left( {{1}^{2}}+{{s}^{2}} \right) \\
& {{\left( \dfrac{x}{a} \right)}^{2}}-1={{s}^{2}}\ldots \ldots \ldots \left( 5 \right) \\
\end{align}$
Now using equation (3), we get
$\begin{align}
& \dfrac{y}{a}=\left( \sqrt{{{1}^{2}}+{{r}^{2}}} \right) \\
& {{\left( \dfrac{y}{a} \right)}^{2}}=\left( {{1}^{2}}+{{r}^{2}} \right) \\
& {{\left( \dfrac{y}{a} \right)}^{2}}-1={{r}^{2}}\ldots \ldots \ldots \left( 6 \right) \\
\end{align}$
Multiplying equation (5) and (6), we get
$\begin{align}
& \left( {{\left( \dfrac{y}{a} \right)}^{2}}-1 \right)\left( {{\left( \dfrac{x}{a} \right)}^{2}}-1 \right)={{r}^{2}}{{s}^{2}} \\
& \left( {{\dfrac{y}{{{a}^{2}}}}^{2}}-1 \right)\left( {{\dfrac{x}{{{a}^{2}}}}^{2}}-1 \right)={{r}^{2}}{{s}^{2}} \\
\end{align}$
Now, simplifying terms inside bracket and using equation (4), we get
$\begin{align}
& \dfrac{{{x}^{2}}{{y}^{2}}}{{{a}^{2}}{{a}^{2}}}-\dfrac{{{x}^{2}}}{{{a}^{2}}}-\dfrac{{{y}^{2}}}{{{a}^{2}}}+1={{(-1)}^{2}} \\
& \dfrac{{{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})}{{{a}^{4}}}+1=1 \\
& \dfrac{{{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})}{{{a}^{4}}}=0 \\
& {{x}^{2}}{{y}^{2}}-{{a}^{2}}({{x}^{2}}+{{y}^{2}})=0 \\
& {{x}^{2}}{{y}^{2}}={{a}^{2}}({{x}^{2}}+{{y}^{2}}) \\
\end{align}$
A parabola whose length of latus rectum is 4a touches both coordinate axis then the locus of its focus is ${{x}^{2}}{{y}^{2}}={{a}^{2}}({{x}^{2}}+{{y}^{2}})$.
So, the correct option must be a).
Note: Equation of a tangent to a parabola passing through point $(a{{t}^{2}},2at)$ can be taken as $x-ty+a{{t}^{2}}=0$ directly instead of deriving it. We must memorise this as it is very helpful in solving such questions and it will save time in the exam. In this question, latus rectum value is given through which we can find the focus of parabola and its equation.
Recently Updated Pages
The real roots of the equation x23 + x13 2 0 are A class 11 maths JEE_Main
Find the reminder when 798 is divided by 5 class 11 maths JEE_Main
If there are 25 railway stations on a railway line class 11 maths JEE_Main
Minimum area of the circle which touches the parabolas class 11 maths JEE_Main
Let A and B be two sets containing 2 elements and 4 class 11 maths JEE_Main
A ray of light moving parallel to the xaxis gets reflected class 11 maths JEE_Main
Trending doubts
JEE Main 2025 Session 2: Application Form (Out), Exam Dates (Released), Eligibility & More
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
Learn About Angle Of Deviation In Prism: JEE Main Physics 2025
JEE Main 2025: Conversion of Galvanometer Into Ammeter And Voltmeter in Physics
JEE Main Login 2045: Step-by-Step Instructions and Details
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
NCERT Solutions for Class 11 Maths Chapter 9 Straight Lines
NCERT Solutions for Class 11 Maths Chapter 12 Limits and Derivatives
NCERT Solutions for Class 11 Maths Chapter 8 Sequences and Series
NCERT Solutions for Class 11 Maths Chapter 10 Conic Sections
NCERT Solutions for Class 11 Maths Chapter 13 Statistics